2013
DOI: 10.4161/derm.23874
|View full text |Cite
|
Sign up to set email alerts
|

A marriage of two “Methusalem” drugs for the treatment of psoriasis?

Abstract: In this article we present arguments that the “antidiabetic” drug metformin could be useful as an add-on therapy to methotrexate for the treatment of psoriasis and, perhaps, for rheumatoid arthritis as well. Biochemical data suggest that both drugs may share a common cellular target, the AMP-activated protein kinase (AMPK). This enzyme is a master regulator of metabolism and controls a number of downstream targets, e.g., important for cellular growth or function in many tissues including T-lymphocytes. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 142 publications
(152 reference statements)
1
26
0
Order By: Relevance
“…These findings support the notion that since transporters involved in uptake and extrusion of metformin were designed by nature for endogenous substrates, the metabolic effects of metformin might involve substrate competition phenomena with metabolites or nutrients (Glossmann & Reider, 2013). Metformin and related biguanides are known to bind endogenous metals such as Zn 2+ , Cu 2+ , Fe 3+ that independently inhibit pro‐inflammatory proteases (Glossmann & Reider, 2013; Lockwood, 2010; Logie et al., 2012; Sweeney et al., 2003; Thorne & Lockwood, 1991). Accordingly, our systematic chemoinformatics approach confirmed that metallopeptidases and proteins with transition metal ion‐binding properties were significantly overrepresented among the predicted targets for metformin.…”
Section: Discussionsupporting
confidence: 79%
“…These findings support the notion that since transporters involved in uptake and extrusion of metformin were designed by nature for endogenous substrates, the metabolic effects of metformin might involve substrate competition phenomena with metabolites or nutrients (Glossmann & Reider, 2013). Metformin and related biguanides are known to bind endogenous metals such as Zn 2+ , Cu 2+ , Fe 3+ that independently inhibit pro‐inflammatory proteases (Glossmann & Reider, 2013; Lockwood, 2010; Logie et al., 2012; Sweeney et al., 2003; Thorne & Lockwood, 1991). Accordingly, our systematic chemoinformatics approach confirmed that metallopeptidases and proteins with transition metal ion‐binding properties were significantly overrepresented among the predicted targets for metformin.…”
Section: Discussionsupporting
confidence: 79%
“…agonist showed a significant reduction in the level of serum CRP compared to patients with psoriasis who did not receive treatment. Metformin, a biguanide family member, is antiinflammatory and immunosuppressive in various experimental mouse models of autoimmune diseases [28]. Metformin may have a specific interaction with mechanisms involved in CRP synthesis or secretion dampening related to chronic inflammation [29].…”
Section: Discussionmentioning
confidence: 99%
“…To date, a careful evaluation of dietary intake using the 7-day food records, considered the “gold standard” of self-administered food frequency questionnaires [ 16 , 17 ], has not been yet provided, and no studies evaluating separately the dietary intake in males and females with psoriasis are available. Moreover, the large majority of studies have included patients in treatment with anti-psoriatic agents, such as biologics, systemic corticosteroids or methotrexate, which may have interfered with anthropometric measures and blood glucose and lipid profile [ 18 ]. Finally, in the setting of the inflammation-related insulin resistance, the association between psoriasis and other cardio-metabolic risk indices, such as the Visceral Adiposity Index (VAI), a gender-specific indicator of adipose distribution and dysfunction [ 19 ], and the Fatty Liver Index (FLI), as an accurate predictor of HS [ 20 ] has not yet evaluated.…”
Section: Introductionmentioning
confidence: 99%